Perlindungan Hukum bagi Reseller E-Commerce dalam Perjanjian Bisnis yang Dibuat dengan Akta Notaris - Fathia Tari Rizka (Jurnal Hukum Lex Generalis, 2026)
Notarial deeds in e-commerce reseller business agreements play a role in ensuring legal protection in digital transactions. This study examines the possibility of legal protection for resellers and the effectiveness of its legal implications in practice. Using a normative juridical approach, the study shows that notarial deeds are key to legal protection for resellers in the digital era, guaranteeing certainty, balance of rights and preventing disputes in online transactions. In the context of e-commerce reseller transactions, notarial deeds remain an essential legal instrument that guarantees legal certainty, protection of rights and the effectiveness of agreement implementation, even though electronic regulations have not yet fully accommodated them.